Improved biooxidation of Benzyl alcohols catalyzed by the flavoprotein (5-Hydroxymethyl)furfural oxidase in organic solvents. Issue 36 (7th September 2017) - Pickl, Mathias; Jost, Etta; Glueck, Silvia M.; Faber, Kurt
Abstract: The biooxidation of benzylic alcohols catalyzed by (5-hydroxymethyl)furfural oxidase (HMFO) to the corresponding benzaldehydes or benzoic acids was investigated in the presence of various organic (co)solvents. Whereas the enzyme activity decreased at elevated concentrations of water-miscible polar solvents, the presence of (halogenated) hydrocarbons was tolerated up to 90% (v/v), which led to drastically improved conversions of up to >99% in case of hexafluorobenzene. This remarkable effect was correlated with the improved solubility of O2 in the employed solvents. Reaction rates were boosted by O2 -saturation of solvents. Graphical abstract: